EFEKTIVITAS PENYELENGGARAAN TUGAS CAMAT DALAM IMPLEMENTASI KEBIJAKAN OTONOMI DAERAH DI KECAMATAN TAHUNA KABUPATEN KEPULAUAN SANGIHE - BUDIMAN, RIRIN; Dengo, Salmin; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : In accordance with the mandate of Law number thirty-two year two thousand and four andGovernment Regulation number nineteen year two thousand and eight, Head for the implementation ofthe regional autonomy policy has the task of carrying out public service administration in the district, andhandles most affairs of autonomy bestowed by the regent or mayor and the authority of the governmentdistrict with it, this study will answer the question: how effective maintenance tasks in the implementationof district Sub regional autonomy policy in Tahuna. Date This study uses Qualitative. Informant in thisstudy consisted of fourteen people from the district government officials (four people), elements ofleadership in the district or autonomous institution of the Department or Agency Unit (two people),management agency vertically (two people), Leader ( three people), and heads of organizations or publicinstitutions (two men) .Instruments in this study is the researchers themselves, while primary datacollection by interview. Date analysis is an analysis model of Miles and Hubernann Interactive. Based onthese results at the district Sangihe Regency Tahuna can be deduced: (A) The effectiveness of the headmaintenance tasks in the field of public service in general is good governance and effective, but there is stillnot maximized (B) Effectiveness district maintenance tasks in handling affairs of regional autonomygranted by the Regent on generally is good and effective, but there is still not maximized. Right on theseconclusions, the recommended suggestions: (A) The coordination of the implementation of the commontasks of governance needs to be improved through regular coordination meetings every month with all theautonomous institutions and agencies existing vertical sub region, with the village government, and shouldalso involve the leadership of the organization or public institutions at the district level; (B) Task district inhandling affairs of regional autonomy granted by the regent should be clearly formulated in a DistrictRegulation district as a reference in formulating programs and activities.